Influence of Brand Personality on Brand Love for Personal Care Brands: With Reference to Sri Lankan Context - Bandaranayake, Y.R.K.; Wickramasinghe, A.S. (International Journal of Economics, Business and Management Studies, 2020)
With the rapid proliferation of products in the market, mere consumer satisfaction is insufficient to remain competitive, thus it brings the need to build a strong emotional bond with the consumer. Brand personality and brand love are widely researched constructs in the journey of building consumer brand relationships. In an era where the paradigm of marketing is gradually shifting from transaction to relationship, it brings a vital importance to study the two variables concerned to sustain amidst the intense rivalry. This study focused on examining the influence of brand personality on brand love referring to personal care products. Furthermore, the mediating effect of brand attitude on the relationship between brand personality and brand love is investigated. The sample was limited 265 respondents, and both inferential and descriptive statistical tools were used to analyze the data. The findings revealed that there is a positive relationship between brand personality and brand love. Intangible associations of a brand are strengthened through brand personality where it is evident empirically that consumers tend to project themselves to the society by the consumption of brands. The five dimensions brand personality was deductively framed in this paper. Adding to that, the mediating effect of brand attitude on this relationship has proven to be significant. In making a purchase decision, consumer’s evaluation on the brand affects to make stronger memories to the consumers. This study contributes to marketing managerial aspects on the means of building a successful consumer brand relationship in the course of building strong brands.